Warning Clothing (WRNG) Business Development Strategy - Adrilsyah Adnan; Keni Kaniawati (LP2M IAIN Palopo, 2026)
Warning Clothing (WRNG), a pioneer streetwear brand from Bandung established in 2000 under PT. Adnan Jusson Indonesia, is experiencing a crisis due to its dependence on the conventional offline wholesale (B2B) model. Digital disruption has triggered a drastic decline in foot traffic at partner physical stores outside Java, causing annual revenue to plummet 40% from Rp14.4 billion (2020) to Rp8.6 billion (2025). This study aims to formulate WRNG's business development strategy through Design Thinking, Business Model Canvas (BMC), and SWOT/IFAS/EFAS analysis, and to test investment feasibility using NPV, IRR, Payback Period, Profitability Index, and the Timmons Model. A descriptive qualitative method with an applied case study approach was employed. IFAS analysis yields a score of 2.27 (weak internal position) and EFAS 2.65 (good external response), placing WRNG in the Turnaround quadrant. The BMC was reconstructed from an As-Is wholesale model to a To-Be hybrid omnichannel model encompassing official marketplace stores, a company website, and a partner dropship system. Financial feasibility analysis at a 12% discount rate produces NPV of Rp4,258,304,214, IRR >100%, Payback Period of ±8 months, and PI of 6.72, collectively declaring WRNG's business plan HIGHLY FEASIBLE for implementation.